Funk: a linguagem proibida - um ponto de vista sociolinguístico - Morais, Fernando Leite (2015)
The language of a determined group is what it characterizes it how such. She manifests herself through several uses in several situations. According to the use of the language for the group, him if it transforms in standards that regulate the communication. Each linguistic community regulates his language through specific characteristics, for example, the slangs use criptológicas to be communicated. From the point of view of the vocabulary, the slang is a basic caraterística between the communication of the funkeiros. The slang has two perspectives: the common slang and that of group. It is aimed, with this study, defines the social group funk, funk sets out the "standard" and the slang as basic elements for construction of the language of the linguistic community. The slang favors to the group a more free communication, which secures the protection of the group and not participants of the group it imposes a limit to. The obscene vocabulary and the Marks (products names, persons or category) also are of our interest in the present study. Basing us on studies of Preti (1983, 1984, 1994, 2004), whose works are references in the explanation and "slangy" clarity of the subject and obscene vocabulary ; of Coseriu (1979) to explain the question of the "standard" and his variations; of Horton and Hunt (1980) to explain what he is social group and Maingueneau (2013) as for the studies of the "Marks" that represent products of consumption like, in case of the funk, motorcars, motorbikes, garment and props of luxury, is that there will happen the explanation of the basic elements for the development of this work. The study also tends to show that the linguistic variation is made perceptible in the letters of funk analysed